2016
DOI: 10.1016/j.geothermics.2016.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Geothermal power plants with maximized specific power output: Optimal working fluid and operating conditions of subcritical and transcritical Organic Rankine Cycles

Abstract: In this paper, the design of an Organic Rankine Cycle (ORC) is optimized by means of numerical simulations. The systems of interest are the subcritical and transcritical thermodynamic cycles.Optimizations are performed with the objective of determining the design that maximizes the specific power output. The design variables include the operating parameters (pressures, mass flow rates), and the best working fluid is determined by comparing the performance of 36 refrigerants. Optimization runs are performed for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(15 citation statements)
references
References 27 publications
0
15
0
Order By: Relevance
“…In fact, the selection of working fluid must be integrated into ORC configuration, performance index and the parameter optimization. The best performance working fluid and optimal working condition differ when the ORC configuration or performance index was different for geothermal power generation [11][12][13]. In spite of several cycle configurations with high performance such as supercritical, dual pressure have been proposed, basic subcritical ORC system is universally adopted in many state-of-the-art lowgrade heat recovery applications due to its allowable working pressure and system compactness.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, the selection of working fluid must be integrated into ORC configuration, performance index and the parameter optimization. The best performance working fluid and optimal working condition differ when the ORC configuration or performance index was different for geothermal power generation [11][12][13]. In spite of several cycle configurations with high performance such as supercritical, dual pressure have been proposed, basic subcritical ORC system is universally adopted in many state-of-the-art lowgrade heat recovery applications due to its allowable working pressure and system compactness.…”
Section: Introductionmentioning
confidence: 99%
“…In 2016 Noé mie Chagnon-Lessard et al [22] demonstrated the optimization of Organic Rankine Cycle by means of numerical simulations. Optimization was performed with subcritical and transcritical thermodynamic cycles that maximizes the specific power output.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The most frequently used are Genetic Algorithm (GA) [28,29] and the methods involving soft-computing [30,31]. Some works can be found also utilising other optimisation techniques such as Monte Carlo simulations [32], the sequential quadratic programming method [33], particle swarm optimisation [34,35], methods allowing the yielding of a set of Pareto frontiers, multi-objective optimisation [36] and the optimisation procedures available in the MATLAB Optimization Toolbox [37].…”
Section: Introductionmentioning
confidence: 99%